High surface area hierarchical porous Al2O3 prepared by the integration of sol–gel transition and phase separation. Issue 62 (14th June 2016) - Passos, A. R.; Pulcinelli, S. H.; Briois, V.; Santilli, C. V.
Abstract : Mechanism of gelation process and phase separation for production of hierarchical porous alumina with high surface area. Abstract : Hierarchical porous γ-Al2 O3 samples were prepared by a soft template method based on the integration of sol–gel transition with spinodal phase separation, using aluminum isopropoxide combined with low molecular weight poly(ethylene oxide) (PEO, M w = 4 × 10 3 g mol −1 ) as phase separation inducer. The boehmite structure formed from the hydrolysis and condensation of aluminum isopropoxide was investigated by means of FTIR and time-resolved SAXS analyses. The boehmite layers acted as the primary building blocks of the gel phase networks. The growth of the gel network reduced the compatibility with PEO, inducing spinodal phase separation between the gel-rich and solvent-rich phases. The results of the TG and FTIR analyses indicated that the PEO was preferentially dissolved in the solvent-rich phase. Mercury porosimetry, N2 physisorption, and SEM measurements revealed that the porous γ-Al2 O3 possessed an interconnected macro-mesoporous hierarchical structure. Appropriate selection of the starting composition enabled control of the average pore sizes and the volume fractions of the macro- and mesopore families present in the γ-Al2 O3 ceramics. The high Al2 O3 surface area (675 m 2 g −1 ) obtained in this work could be explained by the high mesopore volume (3.3 cm 3 g −1 ) and the fine structure of the ceramic skeleton.